Development of Two-Tier Multiple-Choice Test to Assess Students’ Conceptual Understanding on Respiratory System Material of 11th Grade of Senior High School - Azkya Arsyi Myanda; M P Riezky; Maridi Maridi (International Journal of Science and Applied Science: Conference Series, 2020)
Students’ conceptual understanding on Respiratory System Material has to be assessed. This is a research and development study aims to develop a two-tier multiple-choice (TTMC) test to assess students' conceptual understanding on Respiratory System Material on 11th grade. Modified Borg and Gall’s (R&D) research design was used in this research. A preliminary study was conducted to analyse teacher and student needs about instrument assessment. Instrument validation was carried out to expert judgment and 90 of 11th grade students of SMA N Gondangrejo were selected by random sampling. The validation result shows that validation of material, construct, and practitioners expert are very good. Statistical validation using Rasch model shows that there is no item bias in terms of gender, 20 items are valid, person reliability 0.73, item reliability 0.89, item difficulty divided into four categories (very easy, easy, hard, very hard), and based on person separation and item separation the TTMC instrument was developed consists of 4 categories items to assess 3 categories respondent (understanding, misconception, not understanding). The percentage of students’ conceptual understanding on Respiratory System Material shows that 37,7% students understood the concept, 41,6% students had misconceptions, and 20,7% students who don’t understand the concept.